Examining the gender wealth gap - Eva M. Sierminska; Joachim R. Frick; Markus M. Grabka (Oxford Economic Papers, 2010)
Economic research on the determinants of gender differences in economic outcomes particularly in income and consumption is well established. Extending these investigations to other outcomes such as wealth up till now has been limited due to lack of individual-level data. Using the German Socio-Economic Panel (SOEP) we find a significant `raw' gender wealth gap of 50,000 exteuro for married partners. Decomposition analyses reveal that the gap is largely driven by differences in characteristics between men and women (observables), particularly by individual's own income and labour market experience. This is especially true at the bottom and at the top of the wealth distribution, which we show using semi-parametric decomposition techniques. Differences in the lower half of the distribution are mostly driven by the wealth function, i.e., the way in which women transform their characteristics into wealth.
Additional information: This is a pre-copy-editing, author-produced PDF of an article accepted for publication in the journal "Oxford Economic Papers" following peer review. The definitive publisher-authenticated version Examining the Gender Wealth Gap / Eva M. Sierminska, Joachim R. Frick, Markus M. Grabka. In: Oxford Economic Papers 62(2010) Heft 4 ; S. 669-690 is available online at http://dx.doi.org/10.1093/oep/gpq007
Keywords: D13; D31; D69; I31; 330; Wealth gap; Wealth inequality; Gender; SOEP; Familienökonomik; Privater Haushalt; Panel; Deutschland